Aplicação de ensaios de fadiga por flexão em três pontos em corpos de prova de tubos contendo a solda para utilização de avaliação em fadiga de minerodutos fadiga de minerodutos - Cássio Henrique Costa Félix (2019)
Slurry pipelines, although generally not designed with fatigue considerations in mind, can be subject to this type of time-dependent failure mechanism driven by their operational cyclic pressure conditions. Undesirable batch pumping of slurry and water, unexpected stops/starts due to low pump stations reliability, problems in the hydraulic dampening system of reciprocating pumps and no phase shift control between the pumps operating in parallel can lead to significant fatigue cycles throughout the pipeline system. This is exacerbated at the long seam weld which is more sensitive to fatigue degradation. To avoid slurry leaks due fatigue induced cracks, it becomes necessary to evaluate the fatigue performance of the long seam weld under realistic operational cyclic loading. The purpose of this work was to demonstrate the applicability of a three-point bend fatigue test on curved specimens containing a weld for use in fatigue assessments of slurry pipelines. The major challenge of this work was to correlate the stresses at the weld toe due to the application of static load in the three-point bending test in a curved test piece, and the stresses at the weld toe in a pipe submitted to internal pressure during operation. This correlation was made through finite element simulations validated with extensometry and analytical calculations. Thus, a three-point bending fatigue curve, where the result is force by number of cycles to failure, can be converted into an internal pressure curve by number of cycles until failure. With the historic of pipeline operating pressures, it is possible to perform the pressure cycle counting by the rainflow method, and through the new generated curve it is possible to perform the fatigue evaluation by the cumulative damage method. The results demonstrated that it is possible to use the proposed testing approach for the evaluation of the fatigue performance of the slurry pipeline long seam weld.